The Additive-Multiplicative Hazards Model for Multiple Type of Recurrent Gap Times (Communications in Mathematical Research, 2021)
Recurrent event gap times data frequently arise in biomedical studiesand often more than one type of event is of interest. To evaluate the effects ofcovariates on the marginal recurrent event hazards functions, there exist two typesof hazards models: the multiplicative hazards model and the additive hazards model.In the paper, we propose a more flexible additive-multiplicative hazards model formultiple type of recurrent gap times data, wherein some covariates are assumed to beadditive while others are multiplicative. An estimating equation approach is presentedto estimate the regression parameters. We establish asymptotic properties of theproposed estimators.